Effect of early measles vaccination on long-term protection: A systematic review. Issue 22 (21st May 2021) - Xu, Janine; Doyon-Plourde, Paméla; Tunis, Matthew; Quach, Caroline
Highlights: Canadian measles vaccination schedule calls for two doses after 12 months of age. Antibodies from vaccinated mothers have been shown to disappear before 12 months. This places infants at risk of getting infected before routine vaccination. Age of vaccination dictates effectiveness, with better protection with older age. Abstract: Background: In North America, the first dose of a measles-containing vaccine (MCV1) is administered at ≥12 months of age. However, MCV1 may be given to infants <12 months living in highly endemic areas or traveling to these areas. Although an early dose of MCV1 leads to immediate protection, it remains unclear how this impacts long-term immunity. Methods: This systematic review and meta-analysis evaluates the impact of MCV1 given at <12 months vs. ≥12 months of age on long-term immunogenicity and vaccine effectiveness, with long-term defined as at least one-year post-vaccination. PubMed, EMBASE, Global Health, Web of Science and Scopus were searched on October 31st, 2019. Studies were included if they included a cohort of infants vaccinated <12 months of age and evaluated long-term immunogenicity, vaccine efficacy, or effectiveness. Results: A total of 51 texts were identified: 23 reported outcomes related to vaccine effectiveness and 30 to immunogenicity. Infants vaccinated with MCV1 < 12 months of age showed an overall higher risk of measles compared to ≥12 months of age (RR = 3.16, 95% CI: 2.00, 5.01; OR = 2.46, 95% CI: 1.40, 4.32). Risk of measles decreased with increasing age at first vaccination, with those vaccinated with one dose ≥15 months at a lesser risk compared to 12–14 months or <12 months. Measles seroconversion and seropositivity was not affected by age at first vaccination, but antibody levels were significantly lower in the MCV1 < 12-month group (MD = −0.40, 95% CI: −0.71, −0.09). Conclusion: Long-term measles seroconversion and seropositivity did not appear to be affected by age at MCV1, while vaccine effectiveness decreased with younger age. There was not enough evidence to look at the effect of age at MCV1 on immune blunting.